Desmoplastic melanoma on the nose: electrochemotherapy as an alternative treatment to local advanced disease. (18th March 2013) - Carrera, C.; Bennassar, A.; Ishioka, P.; Dalle, S.; Vilalta, A.; Fuertes, I.; Alos, L.; Thomas, L.; Puig, S.; Malvehy, J.
Abstract Background Desmoplastic malignant melanoma (DMM) is a rare and usually misdiagnosed type of melanoma. Delayed detection at complicated anatomical locations can lead to the necessity of alternative therapies. Objective Characterization of DMM on the nose, which is the second more frequent type of MM. Methods Review of case series of eight pathologically proven DMM on the nose from two referral centres with a mean follow‐up of 69 ± 40.5 months. Results According to a single centre experience, there is a more than 70‐fold increased risk of having a DMM on the nose compared with a non‐DMM (P < 0.0005, CI99% 16.3–317.3). Clinical and pathological misdiagnoses were frequent, only three of the eight cases were properly diagnosed and treated and indeed they did not experience relapses. Due to non‐clinical suspicion and superficial biopsies, three cases were initially pathologically misdiagnosed as basal cell carcinomas and a nevus respectively. Atypical vessels and remnants of pigment on dermoscopy are indicative findings even in non‐pigmented cases. Although not significant, the mean disease‐free survival differed between cases with a correct initial management (four cases, 66.7 ± 57.3 months) in contrast to improper (four cases, 16.25 ± 18.9 months). Electrochemotherapy achieved a complete local control of disease in two cases unsuitable for surgery. Conclusions Use of dermoscopy and correctly selected biopsy of lesions on the face is mandatory to improve early diagnosis of DMM. Improper management of challenging cases implies a more complicated therapy and loco‐regional invasion risk. Electrochemotherapy could be a promising therapy in local advanced tumours.